Emergy analysis for transportation fuels produced from corn stover in China - Liu, Changqi; Huang, Yaji; Wang, Xinye; Tai, Yang; Liu, Lingqin; Sun, Chenggong; Liu, Hao (Elsevier, 2018)
In order to provide more useful information for the decision makers in China to implement sustainable energy policies and to identify which region in China is most suitable to build the biofuel production plants for fast pyrolysis and hydroprocessing of corn stover, the present study has evaluated the production efficiency and sustainability of large-scale transportation fuel production via fast pyrolysis and hydroprocessing of corn stover in China using emergy analysis approach. Both the hydrogen production scenario (i.e. oil hydroprocessing using the hydrogen derived from bio-oil reforming) and the hydrogen purchase scenario (i.e. oil hydroprocessing using the hydrogen purchased from market) in three regions of China (Northeast China Plain (NECP), North China Plain (NCP) and Shaanxi Province (SXP)) have been investigated. The results have shown that maize production, and fast pyrolysis and hydroprocessing are the two biggest emergy input stages of the biofuel production system. The comparison of the emergy indices of all of the six cases investigated indicates that the hydrogen purchase scenario in NCP is the best biofuel production case due to its second best sustainability and the second highest production efficiency. In comparison to bioethanol from cassava chips and wheat and biodiesel from jatropha curcas L, the hydrogen purchase scenario in NCP is also the most sustainable plan for a biofuel production plant in China. As water, fertilizer and hydrogen are the three biggest emergy inputs in this case, improvements on the water management, fertilizer management and hydrogen production technology have been discussed. In order to further increase the efficiency and sustainability of the hydrogen purchase scenario in NCP, some of the necessary efforts required from the relevant sectors have also been put forward based on the results of the emergy analysis.